KENDALA JAKSA DALAM EKSEKUSI PIDANA TAMBAHAN UANG PENGGANTI PADA PERKARA TINDAK PIDANA KORUPSI (Studi Kasus Korupsi Di Kejaksaan Tinggi Jawa-Timur) - Aga Wirananta (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
The issue of recovery asset in the management of corruption practices has become a serious problem. It is due to some facts revealed that some corruption cases being convicted are not compatible with the execution in terms of criminal restitution money. With the Juridical Obstacles: Convict died. Legally, law does not explicitly regulate people who intend to pay but can not afford to pay all at once. Non Judicial Constraint: Problems who are assigned to calculate the loss to the state and how existence of compensation money management convict has moved domicile but are not known to exist. The steps to be done by Country is when the investigation, the prosecutor made an attempt to restore the loss by doing confiscation. To address uncertainty of convict or where convict treasure, the prosecutor cooperating with police to investigate the presence of the convict and convict treasure and also ask for help from people around. It turns out that the implementation of criminal money substitute is not as easy as imagined.Keywords: Constraint, The prosecutor, Criminal Money Substitutes, Corruption